Carcinoid Tumor in a Mature Thymic Teratoma: A Rare Type of Extra Cardiac Mass - Gregoriana Zanini; Mariella Chiudinelli; Luisa Bercich; Alessandra Pelati; Monica Bortolotti; Gian Franco Pasini (Case Reports in Vascular Medicine)
We describe the case of a young female affected by a thymus teratoma coexisting with carcinoid tumor.